Development of Learning Media Boxes Paper Materials Measuring Length and Weight Units to Improve High Level Thinking - Farida, Lilis Nur; Murtadlo, Murtadlo; Farisi, Muhammad Imam (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to produce Boxs Paber media products for measuring units of length and weight that are appropriate for use by grade III (three) students in learning Mathematics in Elementary Schools. This study uses the ADDIE development model, through five stages, namely analysis (analyze), design (design), development (develop), implementation (implement), and evaluation (evaluate). The research was conducted at SDN Glagahan 1 with 30 students in class III as an experimental class and 30 students in class III at SDN Perak 2 as a control class. Data collection techniques use observation, questionnaires, tests and interviews. Data analysis techniques include qualitative analysis and quantitative analysis. The results of the research show that: (1) the development of Boxs Paber media consists of several aspects of development, namely media, material and language. In terms of media, it’s simple, good, displaying varied colors, neat, and flexible. In terms of material, the material is in accordance with KI, KD, and learning objectives as well as attractive pictures. Furthermore, in terms of language, communicative, according to EYD and straightforward; (2) The feasibility level of Boxs Paber media is in the very feasible or very valid category. This can be seen from the results of the media expert’s assessment being 94, the material expert’s assessment being 77, and the language expert’s assessment being 91 so that the average validity of the media is 87 (Very Valid). (3) In terms of interest and ability, it can improve higher order thinking skills after using Boxs Paber media. This is shown by students’ interest which was initially 31.48 increasing to 52.32 and students’ high level thinking abilities which were initially 47.4 to 87. From the increase in students’ interest and high level thinking abilities, it shows that the use of the Boxs Paber media is long unit material and effective weight is used in learning.